Overview of Outpatient JKN Patient Satisfaction with Pharmaceutical Services at the Pharmacy Installation of Rumah Sakit Islam Karawang - Fitri Dwi Wijayanti; Neni Rahmani; Rini Yusnitasari (Jurnal Kesehatan dan Kedokteran, 2026)
Pharmaceutical services are an essential part of hospital healthcare because they are related to medication safety, rational drug use, service efficiency, and patient satisfaction. In the context of the National Health Insurance program (Jaminan Kesehatan Nasional/JKN), outpatient pharmacy services are required to provide accurate, timely, informative, and equitable services. Objective: This study aimed to describe the characteristics of JKN outpatients and their satisfaction level with pharmaceutical services at the Pharmacy Installation of Rumah Sakit Islam Karawang. Methodology: This study used a descriptive quantitative design with a cross-sectional approach. A total of 358 respondents were selected using accidental sampling. Data were collected using a structured questionnaire based on five SERVQUAL dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The data were analyzed descriptively using frequency distributions and satisfaction percentages. Findings: Most respondents were female, aged 36–45 years, employed, and had a senior high school educational background. The overall patient satisfaction score was 78.95%, categorized as satisfied. The highest scores were found in the tangibles dimension at 83.02% and empathy at 82.83%, both categorized as very satisfied. Responsiveness and reliability obtained scores of 77.37% and 76.12%, respectively. The assurance dimension had the lowest score at 74.62%, although it remained in the satisfied category. Implications: The findings indicate that pharmaceutical services for JKN outpatients were generally satisfactory. However, improvements are needed in assurance, particularly medication availability, medication accuracy, prescription suitability, and patient confidence. Originality: This study provides empirical evidence on JKN outpatient satisfaction with pharmaceutical services at Rumah Sakit Islam Karawang and identifies priority dimensions for service quality improvement.